A Study on Children Ever Born and its Associated Factors of Suddhodhan Rural Municipality of Rupandehi District, Nepal - Chhetri, Pradip; Kant Bhusal, Chet; Shrestha, Rubina; Shrestha, Saneep; Priyanka, Jyoti; Aryal, Basanti; Bhattarai, Sigma (Annapurna Journal of Health Sciences, 2023)
Background: Despite the several efforts made in the development plans to reduce the population growth rate, the population of Nepal has rapidly been increasing from last few decades. This study aims to find the associated factors to have more than two children in Suddhodhan rural municipality of Rupandehi, Nepal. Material and Method: A cross sectional descriptive study was conducted in a Suddhodhan rural municipality of Rupandehi district, Nepal among 440 ever married women selected by using disproportionate stratified random sampling. Chi Square test was used to find the associated factors to have more than two children. Results: The study found that mean number of children ever born on Suddhodhan Rural Municipality of Rupandehi district, Nepal was 4.1. Among 440 women included in the study, 57.27% women had more than two children. There was statistically significant association between children ever born with religion, age of women and husband, age at marriage, literacy rate of respondents and her spouse, respondent occupation, knowledge of contraceptive methods, exposure to mass media. Conclusion: The study concluded that religion, age of women and husbands, age at marriage, literacy rate of husband and wife, respondents occupation, knowledge of contraceptive methods, exposure to mass media were the main factors for determining the children ever born. Hence local level policy maker, planner and stakeholders of local municipal office should focused on providing informal education such as PraoudSikshya involving both the women and their husbands, should provide the intervention related to contraceptive methods through group discussion as well as through the use of mass media.